Draft genome sequences of five multidrug-resistant Escherichia coli strains isolated from vegetable samples in Bangladesh - Islam, Md. Saiful; Pramanik, Pritom Kumar; Rana, Md. Liton; Ramasamy, Srinivasan; Schreinemachers, Pepijn; Oliva, Ricardo; Rahman, Md. Tanvir (American Society for Microbiology, 2024)
Reports indicate that vegetables are becoming a source of multidrug-resistant (MDR) bacteria, including Escherichia coli. Here, we present genome sequences of five MDR E. coli strains to assist future genomic analysis of this bacterium. These E. coli strains were isolated from vegetable samples of different gardening systems in Dhaka, Bangladesh.